Association of biliary atresia with jejuno-ileal atresia: Case report - Amru Abulkhair; Adel Albiety; Petros Valioulis; Khalid Eibani; Eshraq Omar; Amjad Tala't; Reem Mosalli; Omar Mansour (Elsevier, 2023)
Background: Jejuno‐ileal atresia (JIA) is a congenital anomaly characterized clinically by bilious vomiting and abdominal distension. The incidence of JIA is approximately between 1 in 5000 live births in different parts of the world. It occurs equally in males and females, and about one in three of affected infants is premature. It has been associated with various congenital anomalies but the association of JIA with biliary atresia is extremely rare. Case presentation: We herein present a case of ileal atresia associated with biliary atresia. The patient was a boy who was born at 42 weeks of gestation with APGAR score 9/10 and no reported abnormality during antenatal follow-up. He was operated initially for intestinal atresia then was operated for kasai PE. He tolerated both procedure well. Conclusion: We support developmental etiology of Biliary Atresia rather than congenital etiology. Kasai portoenterostomy is bridge for liver transplant. Patients with BA should have better prognosis when operated early.